HUBUNGAN PERAN PERAWAT DAN SARANA DAN PRASARANA DENGAN KEMANDIRIAN KELUARGA DALAM PELAKSANAAN PROGRAM PERAWATAN KESEHATAN MASYARAKAT DI PUSKESMAS (PERKESMAS) DI PUSKESMAS LUBUK TAROK KABUPATEN SIJUNJUNG TAHUN 2016 - yenni yenni (Universitas Fort De Kock, 2016)
Community Health Nursing (PERKESMAS) is about scope with unification with nursing and public health with support active. This activities kinds of promotion and preventif in a manner of continuty without disregard service currative and rehabilitative all of and integrated. Direction for individually, family, human and publik the first of unity whole from the proses of nursing. Based on the first study at Puskesmas Lubuk Tarok, it’s knew that strata of outonomy family is KM II 96 KK (66,2%), and KM III is 49 KK (33,8%). The purpose of observeris for know related roles of nurse,tool and infrastructure with outonomy family it do at Puskesmas Lubuk Tarok district Sijunjung regency at 2016. This reseach the kind of deskriptive and analitic to approach cross sectional study, the methode chi-square. The way of sample with use simple random sampling. The reseach of population about 171 KK and sample 63 peoples. The tool of using is quiz and checklist. The product reseach can be role of nursing PERKESMAS minus (60,3%), the tools and infrastructure PERKESMAS is not enough from (85,70%), and level the family low (68,3%). Based on chi-square can be related about role of nurse the higher level family the value (p = 0,025). Kind of tools and infrastructure with level higher family with value (p = 0,023). So the value is p < ɑ (0,005). So, can make summary related based on role of nurses and tools and infrastructure PERKESMAS with level higher family in this program PERKESMAS.The for it is can summary responden can make message healthy from nurses of PERKESMAS in our daily life and useful for nursing and healthy.